Polymer particle formation for bacterial cell attachment control - Hüsler, Amanda (2017)
Bacterial attachment and subsequent biofilm formation are the cause for most healthcare-associated infections, leading to both morbidity and mortality. As the post-antibiotic era dawns on us, there is an urgent need to fully understand material-performance relationships for specific biological applications. This facilitates to move towards rational design of improved biomaterials. In this thesis, a step change in formation and screening from planar 2D to particulate 3D surfaces was achieved. A library of microparticles composed of (meth)acrylates was generated using photopolymerisation with either piezoelectric inkjet printing or microfluidics. The surface chemistry and topography of the generated particles was fully characterised prior to bacterial biofilm formation testing with Pseudomonas aeruginosa. Microfluidics has been shown to be the superior particle fabrication methodology, yielding significantly more microparticles with enhanced properties and uniformity. Microparticles formed using microfluidics were perfectly spherical in shape, exhibited narrow size distributions and low average surface roughness alongside a mostly defect-free surface. By comparing inkjet printing with microfluidics in terms of particle properties and yields, the differences in performance were related to the disruptions caused by crossing a phase boundary in the inkjet printing system; from gaseous to liquid. For both techniques, adding a surfactant was necessary to obtain stable droplet formation. Assessing the effect of particle surface chemistry, architecture and size on P. aeruginosa attachment was complicated by the presence of surfactant on both microfluidic and inkjet printed particles. Poly(vinyl alcohol-co-vinyl acetate) (PVA) demonstrated biofilm resistant properties both as bulk and surfactant but with varied efficacy depending on the PVA content. The novel contribution of this work is the generation of a microparticle library of 20 (meth)acrylates made from photocrosslinkable monomers with inkjet printing and microfluidics. For the first time, this study presents a comparison between the two particle fabrication methodologies with respect to microparticle production and characteristics. The work presented in this thesis has provided insights towards the identification of material-property relationships for P. aeruginosa attachment to particles. In prospect for the future, the vision is to progress this effort for applications that require particle delivery into the body such as medical devices with low-fouling coatings, drug delivery and cell carriers in regenerative medicine strategies.